Modernisasi Pendidikan Pesantren dalam Perspektif Dr. ABD. AZIZ, M.Ag. - Roviudin (At- Ta'lim : Jurnal Pendidikan, 2022)
Modernization of islamic boarding school education is a form of education to answer the challenges of the times, where islamic boarding school is the oldest educational institution in Indonesia, and islamic boarding school also has its own advantages both in terms of science and in terms of history. The focus of this writing only rests on education in modern times, both in terms of the education system, islamic boarding school curriculum and the blessing system in modern times where this blessing system is often abandoned by the greatest human beings. Modernization of islamic boarding school education according to Abdul Aziz's is an education system that lies in the regulation of the education system and educational curriculum, so that even though government regulations follow the changing times every year, islamic boarding school will remain with the regulations but do not reject the changing times. Modernization of Islamic boarding school education is also more focused on the mindset of humans residing in the islamic boarding school, so that even though the times have changed, the remains in its identity with education that can humanize humans to be useful and in accordance with the goals of national education, not out of the identity of the islamic boarding school and education